Pengaruh Penyuluhan Manajemen Nyeri terhadap Pengetahuan Siswi yang Mengalami Dismenore di Madrasah Tsanawiyah Bustanul Ulum Pekanbaru - Cindy Nur Fadilah; Fitra Mayenti; Ahmad Redho; Suci Amin (Universitas Baiturrahim, 2026)
Dysmenorrhea is the most common menstrual disorder experienced by adolescent girls and is characterized by pain in the lower abdomen that can interfere with learning activities, concentration, and quality of life. This study aimed to determine the effect of pain management counseling on the level of knowledge among female students experiencing dysmenorrhea at MTs Bustanul Ulum Pekanbaru.This study employed a quantitative method with a quasi experimental design using a one-group pre-test and post-test approach. The sample consisted of 102 female students, selected using cluster sampling technique. The instrument used was a menstrual pain management knowledge questionnaire administered before and after the counseling. Data analysis was conducted using the Wilcoxon Signed Rank Test.The results showed that the majority of respondents were 14 years old, totaling 50 respondents (49.0%). Before the counseling, 71 respondents (69.6%) had a good level of knowledge, while after the counseling, 96 respondents (94.1%) had a good level of knowledge. The statistical test results indicated a p-value of 0.000 < 0.05, which means that there is a significant effect of pain management counseling on the knowledge level of female students experiencing dysmenorrhea at MTs Bustanul Ulum Pekanbaru